Bovine papillomavirus type 1 3' early region transformation and plasmid maintenance functions. - Rabson, M S (1986)
We examined bovine papillomavirus type 1 (BPV-1) DNAs mutated in the E2 open reading frame (ORF) to determine their ability (i) to transform C127 cells and (ii) to remain extrachromosomal in transfected cells. Results obtained with deletion mutants and insertion mutants containing a linker with translational termination codons in all possible reading frames indicated that an E2 ORF gene product(s) is necessary for efficient transformation, as well as viral plasmid replication and maintenance in the context of the full BPV-1 genome. Complementation assays in which mutant BPV-1 DNAs were transfected into cell lines expressing some viral functions from integrated BPV-1 cDNAs demonstrated that the E2 ORF product, when provided in trans, could allow BPV-1 E2 mutants to remain extrachromosomal. The E2 function could also augment transformation of some, but not all, BPV-1 E2 mutants, allowing identification of another region of BPV-1 involved in cellular transformation. It is likely that the role of the BPV-1 E2 product(s) in transformation and plasmid maintenance is indirect. A BPV-1 mutant altered in the E5 ORF is transformation defective and unable to replicate as a stable plasmid in C127 cells.